Kesulitan Belajar Siswa dalam Memahami Konsep Virus di SMA Negeri 1 Tondano: Students' Learning Difficulties in Understanding the Concept of Viruses at SMA Negeri 1 Tondano - Zusje Wiesje Merry Warouw; Nikita Aydelina Br Karo; Fanny Nella Nanlohy (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Virus material in high school biology often causes learning difficulties due to its abstract nature and difficulty in visualizing. This condition results in low student conceptual mastery and high potential for misconceptions. This study aims to map the pattern of student learning difficulties in the virtual material and the factors that cause it. Descriptive research was conducted at SMA Negeri 1 Tondano in April 2025, involving 21 grade X-1 students selected using a simple random technique. Data were collected through observation, written tests (15 multiple-choice questions and 5 essays), and questionnaires on difficulty factors covering aspects of self, family, school, and society. The test instrument was tested for validity with point-biserial correlation and reliability, KR-20, resulting in a coefficient of 0.63, indicating sufficient reliability. The results of the study showed that the average student conceptual mastery only reached 31.14, far below the Minimum Completion Criteria (70). The memory aspect (C1) was higher (34.19%) than the understanding aspect (C2) (26.45%), indicating the dominance of memorisation. A total of 47.61% of students were in the high difficulty category, while 23.8% were in the very high difficulty category. The dominant external factors came from the school environment (88%), particularly limited visual media and laboratory facilities, followed by family support (83.2%), while community influence was lower (52.2%). Internal factors such as student interest, motivation, and attention also contributed significantly.In conclusion, students' learning difficulties in viruses were dominated by weak conceptual understanding and limited learning resources. Innovative learning strategies based on visualization, interactive technology media, concept maps, and virtual laboratories are needed. Practical implications: Biology teachers need to design more contextual and visual learning experiences, utilize technology, and provide space for exploratory activities to strengthen student understanding.